The Effect of Horizontal Vulnerability on the Stiffness Level of Reinforced Concrete Structure on High-Rise Buildings - Fanny Monika; Berkat Cipta Zega; Hakas Prayuda; Martyana Dwi Cahyati; Yanuar Ade Putra (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
Buildings have an essential function; they are a place for people to carry out various activities, such as social, economic, and religious activities. In a building construction plan, considering multiple factors from strength to architecture is necessary. The issue of limited land in some areas has resulted in the construction of vertical buildings, often known as high-rise buildings. High-rise building construction requires paying attention to various levels of vulnerabilities, especially for projects in earthquake-prone areas. In this study, the levels of vulnerability and vertical irregularity of high-rise buildings were analyzed based on structural rigidity for reinforced concrete structures. Building models including a cube-shaped model, L-shaped model, and U-shaped model were investigated. The STERA 3D program was used to determine the strength values of the structures by providing earthquake loads on each structure model using the time-history analysis method. The El Centro and Kobe earthquakes were tested in these structural models because the earthquakes are known to contribute the most exceptional damage value in the history of earthquake-caused disasters. The assessed parameters of the tested structural models include structural stiffness, the most significant displacement in the structure, the maximum displacement and load relations experienced by the construction, and the hysteretic energy exhibited by the structure. Therefore, the best performed structural model in resisting the load could be obtained. The results showed that the U-shaped building model had the highest stiffness value with an increase in stiffness of 7.43% compared with the cube-shaped building model and 3.01% compared with the L-shaped building model.